READING COMPREHENSION FACTORS AND PERFORMANCE OF EFL SECONDARY STUDENTS IN THAI EDUCATION LANDSCAPES: A MULTI-REGRESSION ANALYSIS - Arguedo, Adelyn; Cabiladas, Rex; Minoza, Joemar; Nidoy, Christy Pansy; Moneva, Jerald (JEE (Journal of English Education), 2023)
The study aimed to find out the reading comprehension of the Grade 12 EFL students of Rittiyawannalai School under the international program of Bangkok Thailand and to quantify its relationship to different factors such as availability of reading materials, reading habits, family economic status, parent’s educational attainment, after school tutoring, teacher’s experience and qualification, grammar and vocabulary knowledge, classroom management and motivation. The design used was quantitative using a semi-structured questionnaire to elicit the demographic data and quantifiable elements and analyzed using multi-regression analysis through SPSS. Generally, it was concluded that family economic status (p-value=0.007), after-school tutoring (p-value=0.028), qualification of teachers (p-value=.000), vocabulary knowledge (p-value=0.003), and grammar (p-value=.000) are the dominant factors to the improvement of reading comprehension of the students. On the contrary, other factors obtained more than the level of significance at .05 which made them not significant to student respondents’ reading comprehension performance. This paper recommends exploring more on other factors that would significantly impact reading comprehension performance to continually improve the reading experience of the learners.